2013
DOI: 10.1371/journal.pone.0078113
|View full text |Cite
|
Sign up to set email alerts
|

Poly-LacNAc as an Age-Specific Ligand for Rotavirus P[11] in Neonates and Infants

Abstract: Rotavirus (RV) P[11] is an unique genotype that infects neonates. The mechanism of such age-specific host restriction remains unknown. In this study, we explored host mucosal glycans as a potential age-specific factor for attachment of P[11] RVs. Using in vitro binding assays, we demonstrated that VP8* of a P[11] RV (N155) could bind saliva of infants (60.3%, N = 151) but not of adults (0%, N = 48), with a significantly negative correlation between binding of VP8* and ages of infants (P<0.01). Recognition to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
139
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(146 citation statements)
references
References 34 publications
(37 reference statements)
5
139
0
2
Order By: Relevance
“…HBGAs are oligosaccharides that are expressed on erythrocytes and epithelial cells and are also present in mucosal secretions. In addition, human P[11] rotavirus strains, which cause diarrhoea in neonates, bind to HBGA precursors 12,29 .…”
Section: Rotavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…HBGAs are oligosaccharides that are expressed on erythrocytes and epithelial cells and are also present in mucosal secretions. In addition, human P[11] rotavirus strains, which cause diarrhoea in neonates, bind to HBGA precursors 12,29 .…”
Section: Rotavirusmentioning
confidence: 99%
“…Various cell surface carbohydrates, including sialylated glycans 16 , glycosaminoglycans 710 and human blood group antigens (HBGAs) 11,12 , function as host cell receptors for viral attachment and entry.…”
mentioning
confidence: 99%
“…These binding specificities have been confirmed by haemagglutination of red blood cells, blocking by monoclonal antibodies (mAbs), and binding of the authentic virions. In addition, P [9], P [14] and P [25] genotypes of the P[III] genogroup that infect humans bound specifically to the type A antigens (Refs 28, 30), whereas P [11] of the P[IV] genogroup that infects infants interacted with single and repeated LacNAc, the type 2 precursor glycan ( Refs 52,82). Direct evidence of RV-HBGA interaction has been shown by Xray crystallography of a P [14] VP8* in complex with the type A oligosaccharide (Ref.…”
Section: Diversity Of Novs and Rvs In Recognising Human Hbgasmentioning
confidence: 99%
“…Furthermore, the electrostatic potential surface comparison revealed the similarities and differences among different P genotypes, which may explain to some extent the various binding patterns observed in the functional assays (11,12,(16)(17)(18)36). However, for the potential binding site of P [19], the surface presentation of P [3] and Sia, P [14] and A, P [11] and LNnT, and P [19] showed that there was indeed a cavity in the potential binding site in P [19] VP8* (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…P [11] showed obvious binding to type 1/type 2 precursors (16,17). In addition, P [9], P [14], and P [25] all bound to A type HBGA (A-HBGA) (18).…”
mentioning
confidence: 99%